A 3.7mW 12.5MHz 81dB-SNDR 4th-Order Continuous-time DSM with Single-OTA and 2nd-Order Noise-shaping SAR - Wei Shi; Liu, Jiaxin; Mukherjee, Abhishek; Yang, Xiangxing; Xiyuan TANG; Shen, Linxiao; Zhao, Wenda; Sun, Nan (IEEE Open Journal of the Solid-State Circuits Society, 2022)
This paper presents a hybrid 4th-order delta-sigma modulator (DSM). It combines a continuous-time (CT) loop filter and a discrete-time (DT) passive 2nd-order noise-shaping SAR (NSSAR). Since the 2nd-order NS-SAR is robust against PVT variation, the stability of this 4th-order DSM is similar to that of a 2nd-order CT-DSM. The CT loop filter is based on single-amplifier bi-quad (SAB) structure. As a result, only one OTA is used to achieve 4th-order noise shaping, leading to a high power efficiency. Moreover, this work implements both excess loop delay (ELD) compensation and an input feedforward path inside the NS-SAR in the charge domain, further reducing the circuit complexity and the OTA power. Overall, this work achieves 81 dB SNDR over 12.5 MHz with 3.7 mW power, leading to a Schreier FoM of 176 dB.